PENGELOLAAN REPOSITORI INSTITUSI DI PERPUSTAKAAN UNIVERSITAS NEGERI MEDAN - Harly Christy M. Siagian (Perpustakaan Nasional RI, 2019)
In their development, libraries inseparable from the influences of information technology. This is inded a challenge for libraries to be able to disseminate information quickly, preciesly and globaly. Scientific academic works produced by hinger educations such as skripsi, theses, dissertations, journal articles, books by lecturers, proceedings, research result and so on are valuable assets for higher education institution which, if not managed properly, are going to be a problem in the dissemination of the information contained in these scientific works. Institutional repositories are places for systematically processing, storing and restoring and publishing online the typical works of higher education produced by the academic community. Therefore, a good management of institutional repositories is needed by increasing the quantity and quality of the local contents and infrastructures. This articles aimed to describe the management of institutional repository of State University of Medan Library.